Seni untuk Hati: Art Therapy sebagai Penguatan Emosi Anak di Panti Asuhan Guyub Rukun - Alwi, Wiwit; Danu Rahmat Fajari; Destry Ramadanti; Ferdianata Gustafian; Imallatul Istma; Kurnia Mutiara Indah; Melse Yesnaini; Nadia Razela; Putri Indah Pratiwi; Rafika Fadhila Dhani; Revi Alvionita; Sinta Annisa Putri; Waqina Nata; Yensi Pertamasari (Universitas Bengkulu, 2025)
The activity